Masalah ponteng di kalangan pelajar-pelajar sekolah menengah di daerah Kubang Pasu, Kedah - Ishak, Zulkifli (2008)
This study aims to finding the correlation between five independent variables in relation truancy among form 4 students and the focus of the research is to identify which of the 5 independent variables influence the act of absenteeism in schools. Five aspects have been taken into account namely problem faced by students, family problems, influences among peer group, environmental factors and school factors. This study was done on the form 4 students which have the highest record of absenteeism among 10 secondary schools in Kubang Pasu District. The sampel consisted of 278 students. A self constructed 45 items questionnaires were used for data collection to measure the variables. The data was collected only through questionnaires. A pilot test was carried out to ensure the validity and reliability of the instrument (Cronbach Alfa = .7930). The data was then further used to analys descriptive statistical, the correlation, t test and regression using the Statistical Packages for Social Science (SPSS) version 12. The findings of the study show that the students and school factors are the most dominant factors that the caused truancy among the form 4 students in Kubang Pasu District